A284 CHARACTERIZING SIMULTANEOUS PRESSURE WAVES IN THE HUMAN COLON BY HIGH-RESOLUTION MANOMETRY. (1st March 2018) - Chen, J; Ratcliffe, E; Yuan, Y; Parsons, S P; Vincent, A D; Armstrong, D; Bercik, P; Moayyedi, P; Greenwald, E; Xue, M; Wan, A; Eshtiaghi, A; et al.
Abstract: Background: High-resolution colonic manometry promises much deeper insight into human colon motor function and their control mechanisms than hitherto possible. One motor pattern in need of full understanding is the simultaneous pressure wave (SPW), an apparent instantaneous transient pressure development in the entire colon. Aims: Our aim was to provide a characterization of this motor pattern, its relationship to other motor patterns and its appearance in response to a meal, balloon distension and bisacodyl in healthy subjects. Methods: High-resolution colonic manometry (HRCM) was performed using an 84 sensor (1 cm spaced) water-perfused catheter in 16 healthy volunteers. Intraluminal pressure patterns were recorded during 90 min baseline, during balloon distension, 90 min after a meal and after luminal bisacodyl administration. Quantification was performed using software, based on Image J, developed during this study. Results: SPWs, with amplitudes ranging from 2.4 to 75.2 mmHg (average 12 mmHg) and duration from 2 to 75s (average 11s), occurred throughout the entire colon or they developed at the termination of proximal High-Amplitude Pressure Waves (HAPWs). SPWs progressed into the anal canal followed by anal sphincter relaxation, even at very low amplitudes. SPWs did not obliterate haustral boundary contractions, likely the mechanism by which in vivo gas can escape while stool is retained. SPWs consisted of multiple high frequency, high velocity, pressure waves that resulted in apparent instantaneous pressure development. Balloon distension, a meal or luminal bisacodyl stimulation (10 mg) resulted in high amplitude SPWs associates with gas, water or balloon expulsion. SPWs and HAPWs also occurred independently and then did not influence each other. SPWs occurred in a rhythmic fashion on 26 occasions, including responses to all different stimuli; a distinct rhythmicity was identifiable at an average frequency of 1.8 ± 0.8 cpm, ranging from 0.3 to 4.4 cpm; 13 of the clusters were observed in response to the meal where the average frequency was 2.1 ± 0.9 cpm. Conclusions: The SPWs need to be incorporated into colonic function assessment by HRCM alongside HAPWs. It is the dominant motor pattern that allows gas expulsion and internal anal sphincter relaxation. Low- and high-amplitude SPWs are observed during baseline and are evoked by a meal, balloon distension or luminal bisacodyl. The rhythmicity of SPWs suggests the involvement of the ICC network at the submucosal border of the colon. The associated gas/liquid/balloon expulsion and anal sphincter relaxation provide potential diagnostic value. Their association with HAPWs suggest involvement in the defecation reflex. High resolution allows accurate quantification and 3-dimensional representation. Funding Agencies: CIHRHamilton Health Sciences Organization and Canadian Foundation for Innovation John Evans Leadership Fund